24-hour ex vivo perfusion of vascularized composite allografts in a large animal total limb model - Duru, Çağdaş; Stoian, Alina; Biniazan, Felor; LeBillan, Florian; Karoubi, Golnaz; Keshavjee, Shaf; Haykal, Siba (Frontiers in Transplantation, 2026)
BackgroundStatic cold storage (SCS) at 4 °C remains the standard for preserving vascularized composite allotransplants (VCA) but limits viability to approximately 6 h. Ex-vivo perfusion offers a promising alternative. This study presents a 24-h sub-normothermic perfusion protocol in a swine hindlimb model using autologous red blood cells (RBCs).MethodsLimbs perfused for 24 h were compared with cold-stored limbs. The perfusate contained LPD, 2.5 g/dlBSA, heparin, methylprednisolone, dextrose, insulin, L-alanyl L-glutamine, sodium bicarbonate, and washed RBCs (hematocrit 10%–15%). Perfusion was maintained at 60–65 mmHg and 28 °C–32 °C. Perfusate was monitored hourly. Biopsies (thigh and distal foot) were collected every 6 h for histology and ATP. Limbs were weighed at baseline and endpoint.ResultsPerfusion preserved stable ATP in proximal muscle (0.416–0.367 nmol/μl) and distal muscle (0.315–0.267 nmol/μl). In contrast, SCS showed significant ATP depletion in proximal muscle (0.502–0.15 nmol/μl, p = 0.0086) and distal muscle (0.335–0.078 nmol/μl, p = 0.0216). Injury scores corroborated these findings. In proximal muscle, scores remained stable with perfusion (3.03–3.26) but increased with SCS (2.4 increasing to 3.73, p = 0.0079). In the distal muscle, scores rose in both groups (perfusion: 2.90 increasing to 4.63; SCS: 2.56 increasing to 4.0), with significance only in the control group (p = 0.0291). Limb weight was unchanged (–0.53% perfusion vs. −0.62% SCS).ConclusionTwenty-four-hour swine hindlimb perfusion preserved ATP, morphology, and function. Perfusion prevented ATP depletion and mitigated muscle damage compared with SCS, supporting its potential to extend VCA preservation. Transplant studies are warranted.